Female genital tract microbiome: the influence of probiotics on assisted reproduction - Ana Sofia Almeida Santana; Ana Margarida Póvoa (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Assisted reproductive technology (ART) has been evolving since 1978, with the number of techniques performed increasing over the years. Despite continued advances, some couples continue to have difficulties getting pregnant, and it has recently been considered that the microbiome of the female genital tract (FGT) may influence embryo implantation and the establishment of pregnancy. This review aims to evaluate the role of probiotics on reproductive outcomes in infertile women on ART. A search throughout medical databases was performed, and six articles met the criteria. Five studies showed improvements in pregnancy rates, with only one demonstrating statistical significance. One article showed no improvement but reported a statistically significant reduction in the miscarriage rate in the probiotic group. Further research is needed to evaluate the true potential of probiotics, namely to assess whether they effectively modulate the FGT microbiome and if these changes are maintained over time.